EFEKTIVITAS PENGGUNAAN VIDEO EDUKASI MALOKLUSI UNTUK MENINGKATKAN PENGETAHUAN ORANG TUA TERHADAP KEBIASAAN BURUK ORAL PENYEBAB MALOKLUSI PADA ANAK - Putri, Anisa; Kornialia, Kornialia; Mailiza, Fitria (Universitas Baiturrahmah, 2023)
Oral bad habits are repeated actions carried out in the oral cavity that can cause malocclusion. Kinds of oral bad habits are showing thumbs, biting nails, breathing through the mouth, biting or licking the lips, and sticking out tongue or tongue thrusting. Oral bad habits will be impacted to increase overjet and reduce overbite. Parents' knowledge is an important factor in the oral bad habits of children. Improvement efforts can be carried out by using media counseling such as videos. The research was intended to measure the effect of using video to increase parents' knowledge about oral bad habits that causemalocclusion in children. This was a Pre-experimental study with a One Group Pretest-Posttest cross-sectional design. Measurements were carried out using a questionnaire. Questionnaires and videos were provided via a google form. The population were parents who have children aged 3-6 years in RT 003 RW 001 Pandan Baru Kota, Sample was taken with a total sampling of 40 people. The knowledge level was measured by a questionnaire. Data analysis was univariate and bivariate with Paired T-test. The results showed that the average of parents' knowledge before video intervention is 45% and after the video was given it increased to 71%. The research could be concluded that using video was effective to increased parents' knowledges about oral habits that causes malocclusion in childrens (p= 0.000)